2015
DOI: 10.5137/1019-5149.jtn.14098-15.1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen does not exert neuroprotective effects or improve functional outcomes in rats after intracerebral hemorrhage

Abstract: ABSTRACT(ROS) damage the blood-brain barrier and increase brain edema (8,22,30). Hydroxyl radicals and peroxynitrites are very strong ROS that react indiscriminately with nucleic acids, lipids, and proteins, resulting in DNA fragmentation, lipid peroxidation, and protein inactivation (4,5,10,20,21,24,26,27). edaravone (3-methyl-1-phenyl-2-pyrazolin-5-one) is a potent scavenger of hydroxyl radicals and is used for the treatment of ischemic stroke in Japan. edaravone attenuates the edema and ischemic damage afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These opposing findings might be due to differing experimental conditions, such as different degrees of HI insult, age of pups, H 2 concentration, and length of H 2 exposure. A recent study showed that H 2 administration without surgery did not exert neuroprotective effects or improve functional outcomes in rats after intracerebral hemorrhage [ 109 ]. For spinal cord injury, H 2 treatment improved locomotor behavior recovery in rats [ 110 ] and neurological recovery in mice with experimentally-induced autoimmune encephalomyelitis [ 111 ].…”
Section: Preventive and Therapeutic Applications Of Hmentioning
confidence: 99%
“…These opposing findings might be due to differing experimental conditions, such as different degrees of HI insult, age of pups, H 2 concentration, and length of H 2 exposure. A recent study showed that H 2 administration without surgery did not exert neuroprotective effects or improve functional outcomes in rats after intracerebral hemorrhage [ 109 ]. For spinal cord injury, H 2 treatment improved locomotor behavior recovery in rats [ 110 ] and neurological recovery in mice with experimentally-induced autoimmune encephalomyelitis [ 111 ].…”
Section: Preventive and Therapeutic Applications Of Hmentioning
confidence: 99%
“…Considering that the pathophysiological mechanisms of neural injury and recovery of consciousness in brain diseases are complicated, the effectiveness of H 2 gas treatment might be dependent on the severity of brain damage and the multiple underlying mechanisms of molecular H 2 . Therefore, it may or may not be effective for all inflammation and oxidation-based diseases[ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, treatment with H 2 failed to relieve brain edema or exert a neuroprotective function, although it did decrease the expression of 8-hydroxy-2′-deoxyguanosine, in a rat model of intracerebral hemorrhage. This result may be attributed to the low H 2 concentration that was used in this study, or to the existence of a more complicated mechanism involving reactive oxygen species in intracerebral hemorrhage 76. Therefore, the protective effects of H 2 may differ according to the dosage and/or animal model that are used.…”
Section: Hydrogenmentioning
confidence: 94%